The Human Rights Framework for Covid-19 Pandemic Recovery - Ronny Josua Limbong; Okta Rina Fitri (Journal of Contemporary Sociological Issues, 2023)
The 2030 Agenda for Sustainable Development Goals (SDGs) contribute to the realization of economic, social, and cultural rights. However, the progress of these goals now faces a significant setback due to the impact of the COVID-19 pandemic, especially in Indonesia. This article discusses the impact of the social restriction policy, which results in setbacks in several goals that have further implications for fulfilling the rights to employment and social security. Also, this article elaborates on the role of the human rights approach in recovery efforts that the state must undertake due to the pandemic’s impact. By using the Maastricht Guidelines and the International Covenant on Economic, Social, and Cultural Rights as the theoretical framework, it can be concluded that the impact of the COVID-19 pandemic has caused setbacks in some of the realizations of the SDGs, particularly in economic, social, and cultural rights. These setbacks must be anticipated with recovery policies such as reform of the social security system and improving data collection system. Recovery efforts must be implemented promptly in a measured strategy to prevent the more fatal setbacks that lead to human rights violations. Keywords: COVID-19, Human rights, SDGs